Interactive representation of trauma in postmodern theatre: Audience and character interaction in Bryony Lavery’s Frozen - Ashmawy, Merve Feryal (Studies in Linguistics, Culture and FLT (Online), 2025)
This study explores the interactive representation of trauma in Bryony Lavery’s Frozen (2015), emphasizing the crucial role of audience and character interaction in postmodern theatre. Rather than portraying trauma as a static or detached narrative, Lavery utilizes theatrical techniques that engage the audience emotionally and cognitively, transforming them into witnesses and participants. Drawing on trauma theorists such as Cathy Caruth, Shoshana Felman, and Judith Herman, the study illustrates how trauma is not only represented but transmitted through performance. The characters Nancy, Ralph, and Agnetha – each embody different aspects of trauma, inviting the audience into a shared emotional space. Through direct address, monologues, and fragmented narrative, the play destabilizes conventional storytelling and fosters catharsis. This paper analyzes how postmodern theatrical strategies blur boundaries between character and audience, enabling an immersive experience of trauma and recovery. The implications of such interactive forms are discussed, with suggestions for future research on trauma representation in contemporary performance.